VD_FINDINFO HC / 2011 / 583 vom 24. Oktober 2011 - VD Tribunal cantonal (2011)
MESURE PROVISIONNELLE, COMPÉTENCE RATIONE LOCI, PROROGATION DE FOR | 82 CO, 13 CPC (CH), 261 CPC (CH), 265 CPC (CH), 308 al. 1 let. b CPC (CH)